Self-Declare Halal Products for Small and Micro Enterprises: Between Ease of Doing Business and Assurance of Consumer Spiritual Rights/Self Declare Produk Halal Usaha Kecil Mikro: Antara Kemudahan Berusaha dan Jaminan Hak Spiritual Konsumen - Musataklima, Musataklima (De Jure: Jurnal Hukum dan Syari'ah, 2021)
AbstractLaw Number 11 of 2020 concerning Job Creation has a crucial impact on Law Number 33 of 2014 concerning Halal Product Guarantee, namely Article 4A "halal statement" as the basis for halal certification obligations for micro and small business actors. This paper aims to test the constitutionality of Article 4A, which discusses the constitutional basis of halal products as the constitutional rights of Indonesian Muslim consumers and examines the constitutionality of Article 4A itself. Based on the study results, it can be seen, and firstly, those halal products are the constitutional rights of Muslim consumers, which the 1945 Constitution gives as part of the right to religion because halal products are related to Allah SWT. After all, as His commandments, the constitutional rights of these halal products can be said to be spiritual rights. Second, Article 4A is out of sync with the constitution so that it is thus unconstitutional and has no power to apply based on theÂ lex superiorÂ derogat legi inferioriÂ principle. In addition, it does not have the legitimacy to be considered a law because it does not meet the minimum threshold of morality criteria introduced by Lon L. Fuller. The unconstitutionality of Article 4A has a severe impact on the legal uncertainty of protecting Muslim consumers from accessing halal products as their spiritual right.Keyword: halal statement; consumer protection; undang-undang cipta kerjaAbstrakUndang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja berdampak krusial terhadap Undang-Undang Nomor 33 Tahun 2014 tentang Jaminan Produk Halal, yaitu Pasal 4A â€œpernyataan halalâ€ sebagai dasar kewajiban sertifikasi halal bagi pelaku usaha mikro dan kecil. Tulisan ini bertujuan untuk menguji konstitusionalitas Pasal 4A yang membahas tentang dasar konstitusional kehalalan produk sebagai hak konstitusional konsumen muslim Indonesia dan mengkaji konstitusionalitas Pasal 4A itu sendiri. Berdasarkan hasil kajian dapat diketahui, pertama, produk halal tersebut merupakan hak konstitusional konsumen muslim, yang diberikan oleh UUD 1945 sebagai bagian dari hak beragama karena produk halal berkaitan dengan Allah SWT. Lagi pula, sebagai perintah-Nya, hak konstitusional produk halal tersebut dapat dikatakan sebagai hak spiritual. Kedua, Pasal 4A tidak sinkron dengan konstitusi sehingga inkonstitusional dan tidak mempunyai kekuatan untuk diterapkan berdasarkan asas lex superior derogat legi inferiori. Selain itu, tidak memiliki legitimasi untuk dianggap sebagai undang-undang karena tidak memenuhi ambang batas minimum kriteria moralitas yang diperkenalkan oleh Lon L. Fuller. Inkonstitusionalitas Pasal 4A berdampak parah pada ketidakpastian hukum untuk melindungi konsumenSKeyword: pernyataan halal; perlindungan konsumen; undang-undang cipta kerja